Regional Heterogeneity of D2-Receptor Signaling in the Dorsal Striatum and Nucleus Accumbens - Marcott, Pamela F. (2018)
Dopamine input to the dorsal and ventral striatum originates from separate populations of midbrain neurons. Despite differences in afferent inputs and behavioral output, little is known about how dopamine release is encoded by dopamine receptors on medium spiny neurons (MSNs) across striatal subregions. Here we examined the activation of D2 receptors following the synaptic release of dopamine in the dorsal striatum (DStr) and nucleus accumbens (NAc) shell. We found that D2 receptor-mediated synaptic currents were slower in the NAc and this difference occurred at the level of D2-receptor signaling. As a result of preferential coupling to Gαo, we also found that D2 receptors in MSNs demonstrated higher sensitivity for dopamine in the NAc. The higher sensitivity in the NAc was eliminated following cocaine exposure. These results identify differences in the sensitivity and timing of D2-receptor signaling across the striatum that influence how nigrostriatal and mesolimbic signals are encoded across these circuits. Marcott et al. identify that D2 receptors on MSNs differ in their sensitivity and rate of activation between the dorsal striatum and nucleus accumbens. These regional differences in signaling shape how D2 receptors encode dopamine release events in nigrostriatal and mesolimbic circuits.